The Exaptation of HERV-H: Evolutionary Analyses Reveal the Genomic Features of Highly Transcribed Elements - Gemmell, Patrick; Hein, Jotun; Katzourakis, Aris (Frontiers in Immunology, 2019)
HERV-H endogenous retroviruses are thought to be essential to stem cell identity in humans. We embrace several decades of HERV-H research in order to relate the transcription of HERV-H loci to their genomic structure. We find that highly transcribed HERV-H loci are younger, more fragmented, and less likely to be present in other primate genomes. We also show that repeats in HERV-H LTRs are correlated to where loci are transcribed: type-I LTRs associate with stem cells while type-II repeats associate with embryonic cells. Our findings are generally in line with what is known about endogenous retrovirus biology but we find that the presence of the zinc finger motif containing region of gag is positively correlated with transcription. This leads us to suggest a possible explanation for why an unusually large proportion of HERV-H loci have been preserved in non solo-LTR form.